Larangan Perkawinan Gotong Dalan Tradisi Masyarakat Suku Jawa Perspektif Saddu'dzariah - Putri, Deliana; Liyorba Indra, Gandhi; Fitri, Remeiliza (Kartika: Jurnal Studi Keislaman, 2025)
This study aims to analyze the understanding of the Girimulyo Village community regarding the prohibition of gotong dalan marriage, a traditional Javanese custom that forbids marriage between couples whose houses directly face each other without being separated by a crossroads. The purpose of this research is to explore how this prohibition is perceived and practiced by different generations and to assess its relevance from the perspective of Islamic legal principles, particularly through the concept of sadd adz-dzari‘ah (blocking the means to harm). This study employs a descriptive qualitative method with data collected through in-depth interviews, direct observation, and literature review. The findings reveal that the gotong dalan prohibition has no explicit foundation in Islamic law; however, the fiqh principle of sadd adz-dzari‘ah can be applied to interpret its function as a preventive effort to maintain social harmony and avoid potential conflicts within the community. The study highlights the importance of preserving local wisdom insofar as it does not contradict Islamic law, while fostering dialogue and education between customary norms and religious principles. In this way, traditional values may coexist with the protection of individual rights in marriage, contributing to a harmonious and just social order.